PEDOT–CNT coated electrodes stimulate retinal neurons at low voltage amplitudes and low charge densities. (14th January 2015) - Samba, R; Herrmann, T; Zeck, G
Abstract: Objective. The aim of this study was to compare two different microelectrode materials—the conductive polymer composite poly-3, 4-ethylenedioxythiophene (PEDOT)–carbon nanotube(CNT) and titanium nitride (TiN)—at activating spikes in retinal ganglion cells in whole mount rat retina through stimulation of the local retinal network. Stimulation efficacy of the microelectrodes was analyzed by comparing voltage, current and transferred charge at stimulation threshold. Approach. Retinal ganglion cell spikes were recorded by a central electrode (30 μ m diameter) in the planar grid of an electrode array. Extracellular stimulation (monophasic, cathodic, 0.1–1.0 ms) of the retinal network was performed using constant voltage pulses applied to the eight surrounding electrodes. The stimulation electrodes were equally spaced on the four sides of a square (400 × 400 μ m). Threshold voltage was determined as the pulse amplitude required to evoke network-mediated ganglion cell spiking in a defined post stimulus time window in 50% of identical stimulus repetitions. For the two electrode materials threshold voltage, transferred charge at threshold, maximum current and the residual current at the end of the pulse were compared. Main results. Stimulation of retinal interneurons using PEDOT–CNT electrodes is achieved with lower stimulation voltage and requires lower charge transfer as compared to TiN. The key parameter for effective stimulation is a constant current over at least 0.5 ms, which is obtained by PEDOT–CNT electrodes at lower stimulation voltage due to its faradaic charge transfer mechanism. Significance. In neuroprosthetic implants, PEDOT–CNT may allow for smaller electrodes, effective stimulation in a safe voltage regime and lower energy-consumption. Our study also indicates, that the charge transferred at threshold or the charge injection capacity per se does not determine stimulation efficacy.